2001
DOI: 10.1051/agro:2001153
|View full text |Cite
|
Sign up to set email alerts
|

Feedback regulation of symbiotic N2 fixation under drought stress

Abstract: -Although drought inhibition of N 2 fixation is general among rhizobium-legume symbioses, a large genetic variation has been found among legume species and cultivars in the N 2 fixation sensitivity to water deficits. Legume species that transport ureides from the nodules were found to be much more drought-sensitive than those that transport amides. It was concluded that a feedback mechanism involving ureide level may control N 2 fixation under drought. Consistent with this observation, the drought tolerance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
49
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 32 publications
3
49
0
Order By: Relevance
“…Water-deficit stress causes a well-documented decline in SNF in N 2 -fixing legumes (Arrese-Igor et al, 1999;Zahran, 1999;Serraj et al, 2001), which is also shown for nodulated M. truncatula plants in this study (Fig. 4B).…”
Section: General Down-regulation Of Nodule Plant Metabolism Under Watsupporting
confidence: 85%
See 1 more Smart Citation
“…Water-deficit stress causes a well-documented decline in SNF in N 2 -fixing legumes (Arrese-Igor et al, 1999;Zahran, 1999;Serraj et al, 2001), which is also shown for nodulated M. truncatula plants in this study (Fig. 4B).…”
Section: General Down-regulation Of Nodule Plant Metabolism Under Watsupporting
confidence: 85%
“…Under this stress, symbiotic nitrogen fixation (SNF) is one of the physiological processes to first show stress responses in nodulated legumes, occurring before the decrease in CO 2 -photosynthetic assimilation rates (Durand et al, 1987). Several hypotheses have been proposed by different research groups to explain the decline in nitrogen fixation during drought: (1) regulation through the control of carbon flux within nodules, mainly due to down-regulation of Suc synthase (SuSy; González et al, 1995;Gordon et al, 1997;ArreseIgor et al, 1999); (2) regulation based on the internal oxygen levels within nodules (Durand et al, 1987;Diaz del Castillo et al, 1994;Serraj and Sinclair, 1996); and (3) nitrogen feedback regulation (Serraj et al, 2001;King and Purcell, 2005). However, to date, the molecular mechanisms responsible for these physiological responses are not yet understood.…”
mentioning
confidence: 99%
“…Systemic regulation of nitrogen fixation under environmental stress is believed to involve nitrogen feedback (Parsons et al, 1993;Parsons and Sunley, 2001;Serraj et al, 2001;King and Purcell, 2005), possibly operating through reduced oxygen permeability (Neo and Layzell, 1997). The potential for such regulation existed in this study as nitrogen circulation between split roots is widely accepted (Fisher, 2000) and has been shown for nodulated soybeans (Tanaka et al, 1985).…”
Section: Discussionmentioning
confidence: 81%
“…There is now evidence that signaling for BNF regulation can be provided by a nitrogen feedback mechanism involving shoot nitrogen status. Several molecules have been suggested to be involved in such a mechanism, including Gln (Neo and Layzell, 1997), ureides (Serraj et al, 2001), and Asn (Bacanamwo and Harper, 1997). More recently, King and Purcell (2005) suggested that a combination of ureide and Asp levels in nodules, plus the transport of several amino acids from leaves, might be involved in such a feedback inhibition mechanism in soybean (Glycine max).…”
mentioning
confidence: 99%
“…Indeed, severe water deiciency disrupts the nitrogenase activity of the nodules by causing a rapid decrease in the supply of oxygen to the nodules and consequently an interruption of the adenosine triphosphate (ATP) supply to the nitrogenase [53]. It can also slowdown the transport of photosynthate towards the nodules, which limits the contribution of the energy substrates [54].…”
Section: Efect On Alfalfa Plant In Symbiosismentioning
confidence: 99%